2012
DOI: 10.1016/j.toxicon.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of botulinum neurotoxins light chains

Abstract: Botulinum neurotoxins (BoNTs) are listed among the most potent biothreat agents. Simultaneously, two out of seven known serotypes of these toxins are used in medicine and cosmetics. This situation calls for development of detailed epitope maps of these toxins. Such maps will help to develop new ways for decreasing damage caused by these toxins if they were to be used as weapons while retaining the therapeutic effect of these toxins used as medicine. Here, we used a library of random fragments of DNA encoding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The large, seven aa epitope identified for SEM95-C6 is part of four discrete regions within BoNT/A-L known to induce an immune response in rabbit. 42 This work showed that an antibody directed against this epitope is not neutralizing.…”
Section: Discussionmentioning
confidence: 95%
“…The large, seven aa epitope identified for SEM95-C6 is part of four discrete regions within BoNT/A-L known to induce an immune response in rabbit. 42 This work showed that an antibody directed against this epitope is not neutralizing.…”
Section: Discussionmentioning
confidence: 95%
“…The comparison of the phase diagrams of the system K + //Cl – , SO 4 2– -H 2 O at 348.2, 363.2, and 373.2 K has been done. The composition and solid phase of the invariant points are listed in Table , and the multitemperature phase diagram is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of phase diagrams of the ternary system Mg 2+ //Cl – , SO 4 2– -H 2 O at 348.2, , 363.2, and 373.2 K …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations